Efek dari latihan quiet eye dan latihan tanpa quiet eye pada kiper terhadap akurasi tendangan ke gawang - Alficandra, Alficandra; Henjilito, Raffly; Yani, Ahmad; Zulkifli, Zulkifli; Makorohim, M. Fransazeli (Universitas Nusantara PGRI Kediri, 2023)
Based on the facts on the ground, one of the causes of the less-than-optimal achievements achieved is caused by the lack of accuracy of the player's kick to the opponent's goal. This study aims to analyze the differences in the effect of training using the goalkeeper's quiet eye and training using the quiet eye without the goalkeeper on the accuracy of kicks on the goal. This research is quantitative research with quasi-experimental methodsThis research was conducted at the Tuanku Tambusai stadium, the population of PSBS Kampar, Riau Province, with a sample of 28 soccer players obtained using purposive sampling. The research instrument used to measure the accuracy of kicks to goal in this study is Loughborough Soccer Shooting (LSST). The data analysis technique used the T-test at a significance level (α) 0.05. The study showed a significant difference between the goalkeeper's quiet eye training method and the quiet eye without the goalkeeper on shooting accuracy in PSBS Kampar. The T-test results the experimental group obtained a T count = 4.224 > T table = 2.021 and a sig. (2-tailed) = 0.000 < 0.05, that the training quiet eye increases the accuracy of shooting results.